Reproductive Biology of Channa lucius from the Kampar Lama Oxbow Lake, Mentulik Village, Kampar Regency, Riau Province - Fitriyanti Permanasari; Ridwan Manda Putra; Windarti Windarti (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
AbstractChanna lucius is a type of freshwater fish that commonly inhabit the Kampar Lama Oxbow Lake. This study aims to understand the reproductive biology of C. lucius. The fish was sampled 4 times, twice/month, from June – July 2019. Parameters measured were sexsual characteristics, sex ratio, gonad maturity level, gonad somatic indeks (GSI), fecundity and egg diameter. Results shown that there were 36 males and 23 females (sex ratio 1 : 0.6). The female has bigger body than that of the male. The level of gonad maturity found in male and female fish was ranged from II-IV. Gonado Somatic Indeks (GSI) of the male was range from 0.05% - 0.18% and that of the female was ranged from 0.40% - 2.59%. The average fecundity of the female was 1,465 – 2,621 eggs/fish. Egg diameter ranged from 0.73 – 1.80 mm and egg in different sizes distribute evenly in the ovary, indicating that  C. lucius is a total spawner.Keywords: Channidae, gonad matury level, gonad somatic indeks, fecundity, total spawner